Pengembangan Sistem Kontrol Traksi Mobil Elektrik Berbasis Rekonstruksi Keadaan Kecepatan Model Roda - Pratikto Pratikto; Yul Yunazid Nazaruddin; Edi Leksono; Zainal Abidin (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2010)
In  this  paper  the  development  of  electric  vehicle  traction  control  based  on  state  of  speed  reconstruction  of vehicle model that has the same acceleration condition between tire and chassis is studied. Vehicle is accelerated if the friction force takes place between tire and road. However, the traction force decreases even tends to zero on slippery road and torque input produces a large slip. Evidently, tire slip can be reduced by decreasing the applied torque to the tire. So the basic principle of the proposed method here compares the real vehicle tire speed condition with the model to determine the torque in order to reduce the slip. Tire speed is controlled in order to follow the reference value that is calculated from the model. Tire torque input then can be controlled by applying the feedback that is obtained from the difference value of speed between model and real tire. Implementation of this method on a real vehicle shows that the control method effectively controls the tire speed of vehicle to follow the reference and reducing the slip. From the experiment the control  system performance in reducing slip has the result  of 9.8% for maximum overshoot, 3.1 second for rise time, and 8 second for settling time.